EVALUATION OF THE MINAPOLITAN PROGRAM IN KLATEN REGENCY, CENTRAL JAVA PROVINCE, INDONESIA BASED ON CAPABILITY INDEX (JURNAL SPASIAL, 2021)
Minapolitan programs are intended to create an area consisting of one or more centers of activity in rural areas as a fisheries production system and a certain natural resources management. Since people’s capability is subjective and personal, the capability approach introduced by Amartya Sen (2000) is more suitable for evaluating minapolitan programs. One of the minapolitan regions that needs to be evaluated is “Desa Nila” (Tilapia Village), located in the sub-district of Polanharjo, Karanganom and Tulung, Klaten Regency, Central Java, Indonesia. By using the community capability index and place capability supporting index proposed by Pramono (2016), this paper aims 1) to identify whether minapolitan programs can improve the  fish farmer’s capability, 2) to describe asset variables influencing the minapolitan program to improve fish farmers’ capability. Analysis reveals that minapolitan programs conducted in Klaten Regency have a positive impact on fish farmer’ well-being manifested by the capability. The success of the minapolitan program is indicated by the improvement of several asset owned by the fish farmers which it can be concluded that all the asset variables influencing the fish farmer’s capability have experienced improvement. However, there are two asset variables that have not significantly increased namely quality of public transportation and public library availability.